Anti-HMGB1 Neutralizing Antibody Ameliorates Neutrophilic Airway Inflammation by Suppressing Dendritic Cell-Mediated Th17 Polarization - Fang Zhang; Gang Huang; Bo Hu; Li-Ping Fang; E-Hong Cao; Xiao-Feng Xin; Yong Song; Yi Shi (Mediators of Inflammation)
We demonstrate that high mobility group box 1 protein (HMGB1) directs Th17 skewing by regulating dendritic cell (DC) function. First, our in vitro studies reveal that recombinant HMGB1 (rHMGB1) activates myeloid DCs to produce IL-23 in vitro, and rHMGB1-activated DCs prime naïve lymphocytes to produce the Th17 cytokine IL-17A. Second, we demonstrate that anti-HMGB1 neutralizing antibody attenuates HMGB1 expression, neutrophilic inflammation, airway hyperresponsiveness, and Th17-related cytokine secretion in vivo by using a murine model of neutrophilic asthma induced by ovalbumin (OVA) plus lipopolysaccharide (LPS). Furthermore, anti-HMGB1 neutralizing antibody decreases the number of Th17 cells in lung cells and suppresses the production of IL-23 by lung CD11C+ APCs. Finally, we show that intranasal adoptive transfer of rHMGB1-activated DCs was sufficient to restore lung neutrophilic inflammation and the Th17 response in a DC-driven model of asthma, whereas the transfer of rHMGB1 plus anti-HMGB1-treated mDCs significantly reduced these inflammation phenotypes. These data suggest, for the first time, that HMGB1 drives the DC-polarized Th17-type response in allergic lung inflammation and that blocking HMGB1 may benefit the attenuation of neutrophilic airway inflammation in asthma.